2021
DOI: 10.28926/riset_konseptual.v5i1.311
|View full text |Cite
|
Sign up to set email alerts
|

Model Pembelajaran Langsung : Solusi Masalah Keterbatasan Waktu Pada Pembelajaran IPS

Abstract: Riset ini dilaksanakan dimaksudkan supaya menyelesaikan kesulitan yang dihadapi oleh guru kelas dengan menggunakan model pembelajaran langsung, yaitu ketika guru memiliki keterbatasan waktu tetapi materi yang diajarkan luas seperti pada mata pelajaran IPS materi kerajaan Hindu-Budha dan Islam. Model pembelajaran langsung ialah model pembelajaran yang berorientasi kepada teacher centre. Penelitian ini merupakan hasil dari kajian pustaka dengan cara riset kepustakaan. Hasil penelitian ini mengungkapkan langkah-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The teacher's limited time to explain the material certainly requires students to be able to study independently at home to understand and explore the material being studied. Based on the research results of Mulyaning Tyas in [4], the results obtained showed that the teacher's limitations in explaining the material resulted in low student learning outcomes. In addition, students also experience difficulties understanding the content and the learning process [5].…”
Section: Introductionmentioning
confidence: 99%
“…The teacher's limited time to explain the material certainly requires students to be able to study independently at home to understand and explore the material being studied. Based on the research results of Mulyaning Tyas in [4], the results obtained showed that the teacher's limitations in explaining the material resulted in low student learning outcomes. In addition, students also experience difficulties understanding the content and the learning process [5].…”
Section: Introductionmentioning
confidence: 99%